Palaeomagnetism and 40Ar/39Ar dating from Lower Jurassic rocks in Gastre, central Patagonia: further data to explore tectonomagmatic events associated with the break-up of Gondwana - Zaffarana, Claudia Beatriz (2012)
Se presenta estudio paleomagnético y edades 40Ar/39Ar sobre lavas de la Formación Lonco Trapial, Macizo Norpatagónico. Se discuten resultados en el marco de desmembramiento de Gondwana.